Awareness, knowledge about breast feeding practices among urban mothers - A., Jyotsna; K., Vijayalakshmi; Shinde, Ranoji (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: The knowledge and awareness about breast feeding practices is influenced by educational qualification, type of family and support from the family. Till date in India under- 5 mortality rate is mostly due to improper nutrition to the children since birth and infectious diseases among children. The aim of this study is to assess the knowledge and awareness about breast feeding practices among urban women attending a tertiary care hospital Chennai, India. Methods: This hospital based; prospective, cross-sectional study was carried out among 200 antenatal women who visited a tertiary care hospital in Chennai. The data regarding the knowledge and awareness about breast feeding practices was collected. Results: Knowledge about breast feeding practices like time of initiation, food that facilitate the secretion of breast milk is more among educated mothers. The type of family also showed a significant effect on the awareness about breast feeding. Proper posture of breast feeding was also not known to most of the antenatal mothers. Conclusions: Antenatal women had poor knowledge about the posture of breast feeding, but awareness about the initiation of breast feeding, period of breast feeding and weaning period was satisfactory. Awareness about breast milk banking and storage of breast milk was also poor.